Research on the Teaching Mode Reform of Mechanical Engineering Drawing Courses Oriented by the Demands of New Quality Productive Forces - Zhang, Xingli; Yu, Di; Wang, Lifu (Journal of Educational Research and Policies, 2025)
To meet the demands of new quality productive forces development for high-quality engineering talents, the mechanical drawing course, as a crucial foundational course in engineering education, urgently needs to promote the transformation of its teaching mode towards intelligence, digitalization, and personalization. Based on the current shortcomings of the mechanical drawing course in terms of teaching effectiveness, technology integration, and personalized support, this paper systematically explores the reform path for mechanical engineering drawing courses oriented towards the development of new quality productive forces. It first clarifies the curriculum philosophy centered on “digital transformation and multidisciplinary integration.” Then, it proposes specific reform strategies from multiple aspects, including curriculum content restructuring, teaching resource development, competition mechanism embedding, and artificial intelligence technology integration. The aim is to enhance students’ engineering practical ability and innovative literacy through practice.